2014
DOI: 10.1159/000360492
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype Divergence and Spreading of 5S rDNA Sequences between Genomes of Two Species: Darter and Emerald Gobies (<b><i>Ctenogobius</i></b>, Gobiidae)

Abstract: Karyotype analyses of the cryptobenthic marine species Ctenogobius boleosoma and C. smaragdus were performed by means of classical and molecular cytogenetics, including physical mapping of the multigene 18S and 5S rDNA families. C. boleosoma has 2n = 44 chromosomes (2 submetacentrics + 42 acrocentrics; FN = 46) with a single chromosome pair each carrying 18S and 5S ribosomal sites; whereas C. smaragdus has 2n = 48 chromosomes (2 submetacentrics + 46 acrocentrics; FN = 50), also with a single pair bearing 18S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 57 publications
(52 reference statements)
2
21
0
Order By: Relevance
“…Although collinear and equilocal arrangements of 5S and 18S ribosomal genes are equally rare in fishes [Fujiwara et al, 1998], varying levels of chromosomal distribution have been identified in the genes of a number of fish species at times with greater variability in the distribution of 45S rDNA sites [Mantovani et al, 2005] and sometimes of 5S rDNA sites [Affonso and Galetti, 2005;Lima-Filho et al, 2014]. This condition is also observed in R. canadum , in both the differential frequency of these gene families and the colocalized or independent position in diverse chromosomes.…”
Section: Ribosomal 5s and 18s Chromosomal Mappingmentioning
confidence: 99%
“…Although collinear and equilocal arrangements of 5S and 18S ribosomal genes are equally rare in fishes [Fujiwara et al, 1998], varying levels of chromosomal distribution have been identified in the genes of a number of fish species at times with greater variability in the distribution of 45S rDNA sites [Mantovani et al, 2005] and sometimes of 5S rDNA sites [Affonso and Galetti, 2005;Lima-Filho et al, 2014]. This condition is also observed in R. canadum , in both the differential frequency of these gene families and the colocalized or independent position in diverse chromosomes.…”
Section: Ribosomal 5s and 18s Chromosomal Mappingmentioning
confidence: 99%
“…However, a large number of GC-rich sites were observed in the centromeric and terminal regions of various chromosomes in Ctenogobius smaragdus and C. boleosoma [Lima-Filho et al, 2014] and previously in Neogobius eurycephalus [Ene, 2003]. In the latter species, where karyomorphs with 2n = 30, 31 and 32 derived from Robertsonian fusions, the presence of GC-rich sites is a possible promoter of these rearrangements.…”
Section: Heterochromatin Distribution and Rdna Sites In Gobionellusmentioning
confidence: 80%
“…Together with these variations, modifications in the heterochromatin composition and distribution pattern of repetitive sequences in the karyotype were also observed in several gobiid species [Caputo et al, 1997;Lima-Filho et al, 2014]. The propensity for centric fusions and fissions in the genomes of representatives of this family has been tentatively explained by the occurrence of specific 338 DNA sequences [Canapa et al, 2002], possibly in the centromeres or telomeres, as found in other vertebrate groups [Slijepcevic et al, 1997].…”
Section: Karyotype Diversification and Sex Chromosomesmentioning
confidence: 88%
See 2 more Smart Citations